2012
DOI: 10.1353/hpu.2012.0034
|View full text |Cite
|
Sign up to set email alerts
|

What is the Quality of Preventive Care Provided in a Student-Run Free Clinic?

Abstract: This student-run free clinic provided preventive services at comparable rates to national levels, but short of goals specified in Healthy People 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…Twenty‐five articles described general health care outcomes of SRC participation . This category was divided into three subgroups: patient satisfaction; quality of care provided, and future specialisation and career choice.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five articles described general health care outcomes of SRC participation . This category was divided into three subgroups: patient satisfaction; quality of care provided, and future specialisation and career choice.…”
Section: Resultsmentioning
confidence: 99%
“…The successful replication of the SRC model of early learner engagement may require adjustments to current service delivery and economic models of clinical care. Although productivity pressures and economic models may differ, studies on the quality of care delivered in SRCs have shown the standard of care delivered to be consistent with that required by national guidelines and demonstrated quality‐of‐care indicators comparable with or exceeding those in uninsured populations and comparable with those in insured populations …”
Section: Discussionmentioning
confidence: 97%
“…Although productivity pressures and economic models may differ, studies on the quality of care delivered in SRCs have shown the standard of care delivered to be consistent with that required by national guidelines and demonstrated quality-of-care indicators comparable with or exceeding those in uninsured populations and comparable with those in insured populations. [35][36][37][38] The SRCs provide an example of how we might transform early clinical experiences in the core curriculum from one primarily of observation to one that is learner-centred and enables meaningful engagement and learning. We should consider changing the paradigm of medical education so that we educate with a focus on preparing students for rapid early and legitimate engagement in the workplace by emphasising the achievement of depth in limited areas before we concentrate on building breadth over time.…”
Section: What Affordances Of the Srcs Allow This Degree Of Participatmentioning
confidence: 99%
“…At the start of the study period (November 2014), 16 of the 37 (43.2%) patients empaneled in the ECMH had documented HIV screening in the EMR, mirroring the national average of 40.8% [20]. As illustrated in Table 2, the total number of ECMH patients increased from 37 to 80 over the 18-month observation period.…”
Section: Resultsmentioning
confidence: 99%